(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, who by His grace be good and pray and surrender to the Seal of the Apostles and Prophets and his family and companions and after: After thanking God and thanking him and through the introduction of my letter, which reached a number of results summarized by the following: Sheikh Al Sharawi grew up in a healthy environment, a village environment where he was very calm and a lot of looking into the landscape and nature. Shaykh al-Shaarawi (may Allah have mercy on him) approach easily and easily and tries to bring the information closer to the listener by multiplying the examples and simplifying the language and find a lot of colloquial words to address and facilitate the reader to understand the information. Shaykh al-Shaarawi belongs to the Sufi school and the Bazian way. This method is the method of the owners of the green mummies, which is especially the supervision. These are the ratios of supervision in the words of Shaykh al-Shaarawi (may Allaah have mercy on him). Shaykh al-Shaarawi (may Allaah have mercy on him) differed between the Prophet and the Prophet and said that the Prophet was sent as the Prophet of God says that the Prophet does not come with new legislation but is sent on the Prophet’s approach preceded by an ear. The Prophet is sent but is similar to the behavior and application of the Prophet’s approach, Is the one who sent him a new law to work with him and ordered him the right to apply it and this is an overload in the mission of the Prophet. Shaykh al-Shaarawi (may Allaah have mercy on him) said: "The importance of the prophets and messengers (peace be upon them) is that they have the excuse that they do not say anyone who has not informed us about the Messenger of Allah. Some of the rulings, such as the Israelites who hid (stoning, riba) and the Prophet (peace and blessings of Allaah be upon him), combined the word and gathered the word and stood the believer in front of the wave of atheism in the land.